Body Movement and Nonverbal Communication : An Annotated Bibliography, 1971–1981 - Davis, Martha, 1942- (Book collections on Project MUSE., 1982)
1410 references to published literature in English, Spanish, German, French, Italian, Dutch, and Portuguese. 12 annotators wrote the abstracts and prepared a subject index. Alphabetical arrangement by primary authors. Each entry gives bibliographical information and abstract. Subject and additional author index.